The Role of Herbal Medicine for Hypertrophic Scars Management - Mendrofa, Ira; Putra, Imam Budi (CoinReads Media Prima, 2025)
The process of wound healing is intricate, involving highly coordinated and synchronized mechanisms. Deviations from normal physiological responses can result in hypertrophic scarring. In recent years, there has been a global resurgence of interest in herbal remedies. Many plant-derived compounds and extracts have demonstrated the capacity to inhibit hypertrophic scar formation. The primary mode of action involves inhibiting proliferation and/or triggering apoptosis in scar fibroblasts by modulating various pathways, including PI3K/AKT, VEGF, and TGF-Beta/SMAD. Advancing our comprehension of hypertrophic scar pathophysiology, conducting follow-up research, and pursuing future investigations will help overcome current challenges and lead to the development of promising therapeutic approaches.